Study of Low Temperature Effect on Preservation of Infectivity, Antigen Structure and DNA of Infectious Rhinotracheitis Virus - Stegniy, M. Yu.; Goltsev, A. N.; Stegniy, B. T. (Problems of Cryobiology and Cryomedicine, 2007)
Effect of freezing and long-term storage at moderately low temperatures and in liquid nitrogen on the integrity of infectious properties, antigen structure and DNA of vaccine and industrial strains of infectious bovine rhinotracheitis (IBRT) was studied. It has been established that infectivity in the first passage was expressed by the viruses stored for 8 months and 18 months under moderately low temperatures as well as for 30 months in liquid nitrogen. Immune enzyme analysis has shown the absence of glycoprotein B in thawed virus samples, stored within the range from –18 to –30°C. Specificity of amplified DNA fragment is confirmed by PCR for all studied samples of IBRT virus.